2016
DOI: 10.1016/j.jconrel.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Systemic delivery of siRNA by actively targeted polyion complex micelles for silencing the E6 and E7 human papillomavirus oncogenes

Abstract: Human papillomavirus (HPV) E6 and E7 oncogenes are essential for the immortalization and maintenance of HPV-associated cancer and are ubiquitously expressed in cervical cancer lesions. Small interfering RNA (siRNA) coding for E6 and E7 oncogenes is a promising approach for precise treatment of cervical cancer, yet a delivery system is required for systemic delivery to solid tumors. Here, an actively targeted polyion complex (PIC) micelle was applied to deliver siRNAs coding for HPV E6/E7 to HPV cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 28 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…Nanoparticle loaded with Notch-1 modulators could be excellent if challenges are met with meticulous study. Several investigation and study have been done and reported by researcher about nano particle methods to increase bioavailability, methods to stabilize nanoparticle, prevent degradation, methods to overcome solubility issues, control release from particle [35][36][37][38][39] and use of biodegradable , non-toxic, biocompatible nanomaterial in drug delivery [3,5,7,9,[11][12][13] one such drug molecules which is well reported in nanoparticle formulation is Resveratrol. So based on application of nanotechnology advances and identification of molecular target, cell signaling pathways in DN is possible to deliver drug or silence gene or deliver gene activator or drug with siRNA combination [40] using Nanoparticle.…”
Section: Specific: Specific Inhibitor Nox 4 Isoformmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanoparticle loaded with Notch-1 modulators could be excellent if challenges are met with meticulous study. Several investigation and study have been done and reported by researcher about nano particle methods to increase bioavailability, methods to stabilize nanoparticle, prevent degradation, methods to overcome solubility issues, control release from particle [35][36][37][38][39] and use of biodegradable , non-toxic, biocompatible nanomaterial in drug delivery [3,5,7,9,[11][12][13] one such drug molecules which is well reported in nanoparticle formulation is Resveratrol. So based on application of nanotechnology advances and identification of molecular target, cell signaling pathways in DN is possible to deliver drug or silence gene or deliver gene activator or drug with siRNA combination [40] using Nanoparticle.…”
Section: Specific: Specific Inhibitor Nox 4 Isoformmentioning
confidence: 99%
“…Out of the many nanomaterial investigation report suggested that polymer and calcium phosphate material can be used for delivery drug or to load multiple drug or load siRNA or use combination of drug with siRNA or to induce activator drug or inhibitors of signaling pathway. Silencing mechanism [8][9][10][11][12][13][14][15] : Silencing mechanism can be done by using siRNA (small interfering RNA), which inhibited gene expression in several cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations